The Role of Intestinal Microbiota and Dietary Fibre in the Regulation of Blood Pressure Through the Interaction with Sodium: A Narrative Review - Agnieszka Rudzka; Dorota Zielińska; Katarzyna Neffe-Skocińska; Barbara Sionek; Aleksandra Szydłowska; Karolina Górnik-Horn; Danuta Kołożyn-Krajewska (Microorganisms, 2025)
Sodium consumption is a well-established risk factor for the development of hypertension. Nevertheless, current recommendations for reducing dietary sodium intake are challenging to implement. Consequently, alternative approaches that would reduce the harmful health effects of excessive sodium consumption on blood pressure are highly desirable. The scientific evidence suggests that dietary fibre intake and human intestinal microbiota may affect blood pressure regulation, potentially through interactions with sodium. This narrative review aims to explore the complex interactions between microbiota, fibre, and the fate of sodium in the human body, as well as the implications of these interactions in the prevention and treatment of hypertension. The relevant literature, published up to March 2025, was searched across databases including Google, Google Scholar, PubMed, and Web of Science. A total of 160 most relevant references were included. Gathered evidence suggests that while dietary fibre may reduce sodium uptake into the bloodstream by binding sodium ions and bile salts, microbiota may also contribute to lowering sodium bioavailability thanks to multiple metabolites with anti-inflammatory and intestinal sodium transporter-modulating properties. Despite these promising findings, further work is needed to allow the translation of these insights into effective therapeutic approaches, particularly for salt-sensitive, hypertensive individuals.